Filtração de gases: estudo da deposição de diferentes tortas de filtração em diferentes meios filtrantes - Rodrigues, Karina Bassan (2006)
The particle retention inside a filter medium, after cleaning, significantly improves the initial pressure drop during the subsequent cycle, that is, the residual pressure drop. However, the way as these particles accommodate inside the filter isn t still very clear, as well as, its impact on filtering performance. This work aims to verify the spatial disposal of different particles inside filtration media with different properties, in order to study the penetration depth, after cleaning, as well as the particle size variations from the cake-filter interface to the filtration bulk. Moreover, the objective of this research was to verify the relation between particle penetration behavior and other filtration characteristics for each fabric tested, like the development of residual pressure drop, retained and removed mass after cleaning, and removal efficiency. Three different kinds of powder materials were used for the experiments, varying particle size, granulometric distribution and particle shape: fine phosphoric rock dust, with an average Stokes diameter of 3.71 µm, irregular shape and wide granulometric distribution, coarse phosphoric rock dust, with an average Stokes diameter of 14.67 µm, irregular shape and wide granulometric distribution and tapioca flour, with average Stokes diameter of 8.67 µm, almost spherical shaped, and narrow granulometric distribution. It was observed, despite of the filter media heterogeneity, a particle accumulation in the upward layers of the fabric, decreasing as a function of depth. However, the penetration depth, amount of particles and particle diameter didn t vary according to the number of cycles. It was verified that, the polypropylene fabric, which has low values of permeability and porosity, presented lower particle retention values after cleaning, higher residual pressure drop and shorter filtration cycles, what could be associated with a superficial penetration, according to the microscopy tests carried out. The comparison made between treated and untreated polyester needle felts showed a greater retained mass in the untreated fabric, what resulted in a longer filtration cycle during the beginning of the process, making no difference when fine rock or tapioca flour were used. However, the filtration performance was significantly prejudiced during the following cycles, with higher residual pressure drop and lower particle efficiency removal, what turned the fabric less suitable than the other ones. The results showed that the material presenting narrower granulometric distribution and almost spherical shaped had more xiv homogeneous and long filtration cycles, despite of the greater values of retained mass and depth of penetration, what suggests the better accommodation of particles in the filter cake. The increase in the coarse rock particle diameter resulted in a deeper penetration and a greater retained mass, but similar residual pressure drop, with longer filtration cycles, what meant that the cake formed by greater particles offered better filtration conditions and less specific cake resistance. However, the penetration was deeper for the coarse rock, being the penetration intensity similar for the two rock diameters tested. The increase of maximum pressure drop resulted in a greater retained mass and a greater residual pressure drop. However, nothing could be assured about the total amount of particles collected from each analyzed layer, because the average values in each layer were comparable in magnitude. For a higher maximum pressure drop, the penetration was deeper, as well as the specific resistance of the filter cake, resulted from a greater filtration pressure.